2016
DOI: 10.1136/bmjopen-2015-010360
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the associations between changes in intraocular pressure and metabolic syndrome parameters: a retrospective cohort study in Japan

Abstract: ObjectiveThe contributions of highly correlated cardiovascular risk factors to intraocular pressure (IOP) are not clear due to underlying confounding problems. The present study aimed to determine which metabolic syndrome parameters contribute to elevating IOP and to what extent.DesignRetrospective cohort study.SettingA private healthcare centre in Japan.ParticipantsIndividuals who visited a private healthcare centre and underwent comprehensive medical check-ups between April 1999 and March 2009 were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 62 publications
(55 reference statements)
2
36
3
Order By: Relevance
“…26 In a cross-sectional analysis of all baseline participants of this cohort, 27 age was found to be negatively associated with IOP after adjusting for age and gender, but no longer significantly associated with IOP in the fully adjusted model. [15][16][17] In the current longitudinal analysis, IOP at the 10-year follow-up visit was significantly higher than IOP at baseline, though the difference was small. [15][16][17] In the current longitudinal analysis, IOP at the 10-year follow-up visit was significantly higher than IOP at baseline, though the difference was small.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…26 In a cross-sectional analysis of all baseline participants of this cohort, 27 age was found to be negatively associated with IOP after adjusting for age and gender, but no longer significantly associated with IOP in the fully adjusted model. [15][16][17] In the current longitudinal analysis, IOP at the 10-year follow-up visit was significantly higher than IOP at baseline, though the difference was small. [15][16][17] In the current longitudinal analysis, IOP at the 10-year follow-up visit was significantly higher than IOP at baseline, though the difference was small.…”
Section: Discussionmentioning
confidence: 52%
“…17,28 Higher BP may increase IOP in a physiological way by increasing capillary pressure and choroidal volume. 17,28 Higher BP may increase IOP in a physiological way by increasing capillary pressure and choroidal volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Clinically, beyond the simple snapshot association, 10 a recent large retrospective study demonstrated a significant longitudinal relationship between cholesterol levels and intraocular pressure. 11 However more well-designed clinical studies to explore the role of hyperlipidemia and collaborative basic research are warranted. Such studies will provide a rationale for cooperative care of patients by ophthalmologists and metabolic physicians.…”
mentioning
confidence: 99%
“…11,18 Our results support the findings of many studies that have demonstrated that blood pressure is one of the components of MS and is positively associated with IOP. [7][8][9]19 Further they reported blood pressure is the one strongest predictor of elevated IOP. Several studies explained the relationship between systemic hypertension and rise in IOP.…”
Section: Discussionmentioning
confidence: 99%